1991
DOI: 10.1080/07315724.1991.10718135
|View full text |Cite
|
Sign up to set email alerts
|

A role for magnesium in neonatal parathyroid gland function?

Abstract: Little is known of the factors regulating parathyroid function in the neonatal period. Twenty-seven term infants born after uncomplicated pregnancies, labors, and deliveries were studied to test the hypothesis that in normal newborns the amplitude of parathyroid hormone (PTH) response to decreasing serum ionized calcium (iCa) correlates with serum magnesium (Mg) concentrations. Serum iCa (ion selective electrode, Radiometer ICA 1), PTH (1-84 intact molecules, radioimmunoassay) and Mg (atomic absorption) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…This inhibits bone resorption and results in hypocalcemia despite low PTH concentrations. Loughead et al (47) suggested that hypomagnesemia blunts the parathyroid secretory response to hypocalcemia, leading to an inappropriately low PTH concentration. However, these proposed mechanisms do not account for the observations made in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibits bone resorption and results in hypocalcemia despite low PTH concentrations. Loughead et al (47) suggested that hypomagnesemia blunts the parathyroid secretory response to hypocalcemia, leading to an inappropriately low PTH concentration. However, these proposed mechanisms do not account for the observations made in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies used intact PTH assays but obtained measurements solely at birth and 24 h later, and demonstrated that PTH rose significantly (31,386,388,416,444,473,580). Those studies did not determine when the PTH value increased or whether the peak level was achieved at 24 h or later.…”
Section: Human Datamentioning
confidence: 99%
“…Normal cord blood values for our laboratory vary between 9.0 and 11.4 mg/dl for calcium 15 and 1.74 and 1.90 mg/dl for magnesium. 16 Serum ionized calcium was measured using a Radiometer ICA 1, ion-selective electrode (Radiometer, Coppenhagen). 17 The normal range in nonpregnant adults in our laboratory is 4.8 to 5.2 and is 4.4 to 5.4 mg/dl for neonates (CV, 1.4%).…”
Section: Methodsmentioning
confidence: 99%